A training program incorporating a diabetes tool to facilitate delivery of quality diabetes care by community pharmacists in Malaysia and Australia - Ayadurai, Shamala; Sunderland, Bruce; Tee, Lisa; Hattingh, Laetitia (2019)
Objectives: To assess a clinical training program on management of Type 2 Diabetes Mellitus (T2DM) incorporating a diabetes tool, the Simpler™ tool. Subsequently pharmacists’ experience utilising the tool to deliver structured, consistent, evidence-based T2DM care was explored. Methods: Full-time non-credentialed diabetes pharmacists providing diabetes medication management services in community settings were purposively recruited. Participants had either face-to-face or online training on diabetes management using the tool which took about two hours and 20 minutes to complete. Their diabetes management knowledge was assessed pre-and post-training using quantitative methodology. They were then required to apply the tool in daily practice for one month. Feedback on both the training sessions and tool utilisation were obtained through semi-structured interviews and analysed using a qualitative approach. Results: Twelve pharmacists participated: Six from Australia and six from Malaysia. Before attending the training session, their median test score was 6.5/27, IQR 1.4 (1st marker) and 5.3/27, IQR 2.0 (2nd marker). After training, the scores doubled to 14.3/27, IQR 4.5 (1st marker) and 11.3/27, IQR 3.1 (2nd marker), showing significant improvements (p=0.002). Interview data identified perceived effectiveness factor through use of the tool. Participants found the content relevant, structured, concise and easy to understand; enabled comprehensive medication reviews; focused on achieving glycaemic improvement; facilitated documentation processes and pharmacists’ role in T2DM management; and as a specific aid for diabetes management. Barriers included lack of accessibility to patients’ laboratory data in Australia. Conclusions: The targeted training improved pharmacists’ knowledge on diabetes management and supported the Simpler™ tool use in practice as a structured and beneficial method to deliver evidence-based T2DM care.